Comparison of apparent diffusion coefficient maps to T2-weighted images for target delineation in cervix cancer brachytherapy - Esthappan, Jacqueline; Ma, Daniel J.; Narra, Vamsidhar R.; Raptis, Constantine A.; Grigsby, Perry W. (Journal of Contemporary Brachytherapy, 2011)
Purpose: T2-weighted (T2W) magnetic resonance imaging (MRI) has been used for target delineation in cervix cancer brachytherapy. The objective of this study was to examine the feasibility of using diffusion-weighted magnetic resonance imaging (DWI) for target delineation as compared against T2W imaging. Material and methods: Fifteen cervix cancer patients, implanted with tandem and ovoid applicators, underwent T2W turbo-spin echo imaging and DWI with a maximum diffusion factor of 800 sec/mm 2 on a 1.5-T MR scanner. Apparent diffusion coefficient (ADC) maps were derived from the DWI. The gross tumor volume was manually delineated on the T2W and ADC datasets for each patient. The agreement between T2W- and ADC-delineated volumes was assessed using the Dice similarity coefficient (DSC). An algorithm was developed to compare the edge contrast of the delineated volumes on T2W images and ADC maps by calculating the percentage difference in the intensity values of selected regions of pixels inside versus outside the target contour. Results : ADC-delineated volumes were generally smaller than T2W-delineated volumes, yielding a low DSC of 0.54 ± 0.22. ADC maps were found to display superior definition of the target volume edge relative to T2W images, yielding a statistically significant difference between the mean edge contrast on ADC (12.7 ± 7.7%) versus that on T2W images (4.6 ± 3.2%; p = 0.0010). Conclusions: These results suggest that incorporating the use of DWI for cervix cancer brachytherapy may yield gross tumor volumes that are different from those based on T2W images alone.